上顎歯肉癌に対し腫瘍切除を施行した遺伝性出血性毛細血管拡張症の1例 - 佐野, 和生; 飛田, 尚慶; 間, 悠介; 吉村, 仁志; 近藤, 浩子; 植野, 高章 (日本口腔外科学会雑誌, 2012)
Hereditary hemorrhagic telangiectasia （HHT） is an autosomal dominant inherited disorder affecting blood vessels of the skin, mucous membranes and viscera. A definite diagnosis of HHT is made in the presence of at least three of the Curaçao criteria: （1） epistaxis, （2） telangiectasias, （3） visceral lesions, and （4） a family history. We describe a case of upper gingival carcinoma in a patient with HHT. A 79-year-old woman visited our department because of an upper gingival mass. A biopsy specimen revealed squamous cell carcinoma. Preoperative examination revealed consistency with three of the above criteria: （2） skin and mucosal telangiectasias, （3） gastrointestinal telangiectasia and pulmonary and hepatic arteriovenous malformations （AVMs）, and （4） mucosal telangiectasia and pulmonary AVM in her daughter. HHT was definitely diagnosed. Tumorectomy was scheduled; however, HHT-associated complications such as bleeding, hypoxemia, cerebral thromboembolism, and AVM rupture were expected. Tumor resection by partial maxillectomy and reconstruction with a buccal fat pad were performed under general anesthesia. The postoperative course was uneventful, and follow-up at 1.5 years showed no evidence of tumor recurrence or metastasis. We conclude that recognition of hemorrhagic tendencies and evaluation of systemic AVMs are critical before surgical treatment in patients with HHT.